The system of formation of lexical and grammatical structures in children with speech impairments - Xoldorov Ma’rufjon Maxmudovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Today there are a lot of preschoolers with speech defects. Often these are children with defects in all components of speech: sound pronunciation is impaired, vocabulary lags behind the age norm, the lexical and grammatical structure of speech is not well formed, coherent speech is not developed. Such children do not fully master the general educational program of the kindergarten and in the future it is difficult for them to go to school. The main difficulties are manifested in detailed answers to complex questions of the school curriculum; children do not know how to consistently, competently and logically express their opinions, and are not able to repeat the content of textbooks.